2019
DOI: 10.1002/adsc.201900044
|View full text |Cite
|
Sign up to set email alerts
|

Diversity‐Oriented Synthesis of Complex Pyrrole‐Based Architectures from Very Simple Starting Materials

Abstract: The build/couple/pair strategy was applied to the generation of 18 structurally diverse scaffolds built around pyrrole cores. The couple phase, involving the first application of a mechanochemical multicomponent reaction for this purpose, afforded pyrrole derivatives that were transformed into some unusual fused heterocyclic systems using a domino process initiated by a Cu‐catalyzed cross coupling or intramolecular furan Diels‐Alder reactions. Because of the high current importance of macrocycles in drug disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Despite the high selectivity of this reaction to achieve a single compound, generally, due to the difficulties of isolating molecules formed by opposing side reactions, a low yield has been noticed. [57] The method has therefore been investigated using novel techniques, such as solvent-free settings, highspeed vibration milling, and a mixer operating at 20 Hz, this method afforded higher yields of pyrrole. [58] The pyrrole synthesis performed in solid phase conditions using acetoacetylated rink resin, synthesizing pyrrole-3-carboxamide derivatives (Scheme 1c) which resulted in the product isolation with high purity.…”
Section: Hantzsch Pyrrole Synthesismentioning
confidence: 99%
“…Despite the high selectivity of this reaction to achieve a single compound, generally, due to the difficulties of isolating molecules formed by opposing side reactions, a low yield has been noticed. [57] The method has therefore been investigated using novel techniques, such as solvent-free settings, highspeed vibration milling, and a mixer operating at 20 Hz, this method afforded higher yields of pyrrole. [58] The pyrrole synthesis performed in solid phase conditions using acetoacetylated rink resin, synthesizing pyrrole-3-carboxamide derivatives (Scheme 1c) which resulted in the product isolation with high purity.…”
Section: Hantzsch Pyrrole Synthesismentioning
confidence: 99%
“…Various motifs of dicarbonyl compounds have been extensively utilized toward pyrrole synthesis. [83][84][85][86][87][88][89][90][91][92][93] As discussed in this section, this class of starting materials have enabled the development of a broad array of new synthetic reactions.…”
Section: Dicarbonyl Compoundsmentioning
confidence: 99%
“…14 In this sense, Guo et al described the synthesis of pyrrolo[1,2c]quinazolines via Cu(I)-catalyzed intramolecular cyclization of indolyl derivatives (Scheme 1a), 15 whereas Leonardi et al reported the Cu(II)-catalyzed cross-coupling reaction between aryl iodides and benzylamines followed by cyclization to afford the corresponding pyrroloquinazolines (Scheme 1b). 16 Moreover, Georgescu et al developed a three-component protocol for the synthesis of pyrrolo[1,2-c]quinazolines, in moderate yields under MW irradiation, through in situ formation of quinazolinium N-ylide, which undergoes a 1,3-dipolar cycloaddition with activated alkynes (Scheme 1c). 17 We have previously reported a Cu(I)-catalyzed one-pot Michael addition/dehydration cascade reactions, using βnitroolefins and 2-methyl-azaarenes, furnishing 3-(N-heteroarenyl)acrylonitriles and pyrrolo[1,2-c]quinazolines as minor products.…”
Section: ■ Introductionmentioning
confidence: 99%